AI, Data and Private Law : translating theory into practice - Chan, Gary Kok Yew; Yip, Man (Oxford, UK ; New York, NY : Hart Publishing, an imprint of Bloomsbury Publishing, 2021)
"This book examines the interconnections between artificial intelligence, data governance and private law rules with a comparative focus on selected jurisdictions in the Asia-Pacific region. The chapters discuss the myriad challenges of translating and adapting theory, doctrines and concepts to practice in the Asia-Pacific region given their differing circumstances, challenges and national interests. The contributors are legal experts from the UK, Israel, Korea, and Singapore with extensive academic and practical experience. The essays in this collection cover a wide range of topics, including data protection and governance, data trusts, information fiduciaries, medical AI, the regulation of autonomous vehicles, the use of blockchain technology in land administration, the regulation of digital assets and contract formation issues arising from AI applications. The book will be of interest to members of the judiciary, policy makers and academics who specialise in AI, data governance and/or private law or who work at the intersection of these three areas, as well as legal technologists and practising lawyers in the Asia-Pacific, the UK and the US."--
1. AI, Data and Private Law: The Theory-Practice Interface Gary Chan (Singapore Management University, Singapore) and Man Yip (Singapore Management University, Singapore) -- II. Data Protection, Governance and Private Law -- 2. How to De-identify Personal Data in Korea: An Evolutionary Tale Haksoo Ko (Seoul National University, Korea) and Sangchul Park (Seoul National University, Korea) -- 3. Data Trusts for Lawful AI Data Sharing Chris Reed (Queen Mary University of London, UK) -- 4. The Future of Personal Data Protection Law in Singapore: A Role for the Use of Artificial Intelligence and the Propertisation of Personal Data Warren Chik (Singapore Management University, Singapore) -- 5. Personal Data as a Proprietary Resource Lee Pey Woan (Singapore Management University, Singapore) -- 6. Transplanting the Concept of Information Fiduciary? Man Yip (Singapore Management University, Singapore) -- II. AI, Technology and Private Law. 7. Regulating Autonomous Vehicles: Liability Paradigms and Value Choices Chen Siyuan (Singapore Management University, Singapore) -- 8. Medical Artificial Intelligence, Standard of Care in Negligence and Tort Law Gary Chan (Singapore Management University, Singapore) -- 9. Contract Formation in the Age of Machine Learning Goh Yihan (Singapore Management University, Singapore) -- 10. Digital Assets: Balancing Liquidity with Other Considerations Gal Acrich, Katia Litvak, On Dvori, Ophir Samuelov and Dov Greenbaum (all at IDC Herzliya, Israel) -- 11. Blockchain in Land Administration? Overlooked Details in Translating Theory into Practice Alvin See (Singapore Management University, Singapore).
Includes bibliographical references and index.
Also issued in print: Hart Publishing, 2021.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Artificial intelligence -- Law and legislation -- Asia; Information technology -- Law and legislation -- Asia; Data protection -- Law and legislation -- Asia; Personal information management; Privacy, Right of; Law; IT and Technology Law (Law); Contract; Tort and Restitution Law (Law); Asian Law (Law); Comparative Law (Law); IT & Communications law; Electronic books